Malnutrition Status Among Under - 5 Children in a Hill Community of Nepal - Gaurav, K; Poudel, IS; Bhattarai, S; Pradhan, PMS; Pokharel, PK (Kathmandu University Medical Journal, 2015)
Background Malnutrition, especially under nutrition puts children at increased risk of morbidity and mortality and remains a serious barrier in child growth, development and survival. This is a major public health problem among under- 5 children in Nepal particularly in rural areas.Objective To assess the burden and contributing factors for malnutrition in hill community of Ilam district in eastern Nepal.Method A cross sectional study was conducted in rural hill communities of Ilam district, Nepal with a sample of 240 under- 5 children. Anthropometric measurements were used as per WHO guidelines to asses three nutritional status: Underweight, Stunting, and Wasting using descriptive statistics and chi square test was applied using SPSS 12.0 to assess social and predisposing factors.Result Seventeen percent of under- 5 children were moderately and 10.4 % were severely underweight. Similarly, 22.9%, and 17.5% were found to be moderately and severely stunted respectively. Less than 10% were found to be moderately and severely wasted. Older age group of children, education level of mother, not exclusive breast feeding practice had significant (p